GOVERNANCE OF RURAL BANKS BASED ON LAW CONCERNING BANKING IN THE PERSPECTIVE OF COMMUNITY WELFARE - Rosiyati Rosiyati; Gunawan Nachrawi; Marjan Miharja (Sekolah Tinggi Ilmu Hukum Awang Long, 2023)
Based on Law Number 10 of 1998, the objective of Indonesian banking is to support the implementation of national development in order to increase equity, economic growth and national stability towards increasing people's welfare. Banking can be grouped into three, namely central banks, commercial banks and rural banks. Rural Banks (BPR) are banks that carry out business activities conventionally or based on sharia principles, which in their activities do not provide services in payment traffic. The research method that the authors use is a normative juridical method, namely research that prioritizes library data, namely research on secondary data. The secondary data can be in the form of primary, secondary or tertiary legal materials. This research includes research on positive legal provisions in force in Indonesia relating to BPR governance based on Law Number 10 of 1998 concerning Banking. The research results, positive legal provisions in force in Indonesia relating to BPR governance based on Law Number 10 of 1998 concerning Banking. PT BPR Papua Mandiri Makmur realizes that internalization of broader governance principles needs to be carried out in a sustainable manner to improve the quality and scope of governance implementation in every aspect of PT BPR Papua Mandiri Makmur's activities.